Manejo familiar das necessidades de cuidado de crianças e adolescentes com transtorno do espectro autista: um estudo à luz do Family Management Style Framework. - Cassimiro, Adnez Regina Tertuliano da Silva (2018)
The study aims to investigate the management of families with children and adolescents with autism spectrum before the care needs. The family management with the use of the theoretical model in Nursing Family Management Style Framework corresponds to the caregiver's action against problems encountered during the care performed. The term "management" involves three dimensions that describe how the family member perceives the situations experienced, how he or she responds to the needs of care, and apprehends the actual or imagined consequences of that process. Thus, it is proposed to analyze the family management related to the care needs of the child and / or adolescent with Autism Spectrum Disorder. It is a quantitative, descriptive and cross-sectional study carried out with 127 parents or relatives of children and adolescents with ASD attended at two specialized services in the city of MaceióAL in the years 2017 and 2018. Data collection was performed through face-to-face interview using the ODK Collect v1.12.2 application, installed on tablets containing a sociodemographic questionnaire and the Family Management Measure. The data collected were tabulated and processed electronically with Microsoft® Excel® 2016, the analysis was performed with statistical package S.P.S.S. for Windows version 17.0, using descriptive statistics. Descriptive statistics were used both for characterization of the sample and for the calculation of frequency values, proportions, averages, standard deviations and minimum and maximum values. In each continuous variable the Kolmogorov Smirnov test was performed to verify normality. To compare the mean scores of the scale in non-parametric variables, the Kruskal Wallis test was used for more than two categories and the Mann Whitney test up to two categories. For parametric variables, Student's T-Test and Anova were used for parametric variables with more than two categories. The results analyzed the six response patterns of the dimensions of the Family Management Measure, relating them to the conceptual components of the Family Management Style Framework with the lowest mean score (̅ 16.01) for the Child Identity and Parental Mutuality (̅ 28,22) and scores with high values for the Management Ability (̅ 44,26) and management effort dimensions (̅ 44,26). The Family Difficulties and Impact Impact Assessment scores presented the values of 43.90 and 26.52, respectively. The relatives of children and adolescents present less normality in daily life with their child, with less mutuality with their affective partner and with greater management effort for the condition of the child than parents of children with other chronic conditions. It was concluded that this study allowed a better understanding of the management of families of children and adolescents with Autism Spectrum Disorder. From the findings found in these families, it may be possible to promote family support strategies in a way that aims at reducing family stress, overloading care and promoting quality of life for these families.